Asthma and pulmonary tuberculosis: misdiagnosis or coexistence. Issue 7 (3rd June 2021) - Nguyen‐Ho, Lam; Nguyen‐Tiet, Au; Chang, Yoon‐Seok
Abstract: Asthma and pulmonary tuberculosis (PTB) are disease entities with different pathogenesis. However, endobronchial tuberculosis (EBTB), a peculiar form of PTB, can mimic the symptoms of asthma. Although uncommon, the coexistence of asthma and PTB can appear. We report three cases of PTB. The first two cases with EBTB were misdiagnosed as asthma and the third case with asthma developed PTB four months after high‐dose inhaled corticosteroid (ICS) therapy. The first two cases presented with chronic cough up mucopurulent/purulent sputum and localized wheezing which revealed diagnostic clues. The third case presented with dry cough and showed a positive bronchodilator response and the right pulmonary apical fibrosis which could be associated with quiescent tuberculous infection. EBTB should be included in the differential diagnosis of asthma. Although rare, physicians should be aware that PTB can also be developed during the treatment course of asthma. Abstract : Endobronchial tuberculosis should be included in the differential diagnosis of asthma. Although rare, physicians should be aware that pulmonary tuberculosis can also be developed during the treatment course of asthma.